Role of intercultural communication in hospitality industry : Swiss hospitality meeting the culture of the Gulf State - Imanova, Vazifa (2023)
Intercultural communication competency in hospitality industry opens the room for many barriers. Managing growing levels of the uncertainty during the intercultural service encounters becomes difficult. Accordingly, this situation triggers the complexity within human resource management world as well in dealing with these challenges, thus, ICC practices come in demand than ever before. Since minimizing the culturally triggered misunderstandings is the main expectation from the industry, the need for the intercultural communication trainings for the staff members increases than ever before. However, some organizations are not certain about the ways of doing it in more efficient ways. The ICC research has been mainly raised within the fields of international business and the education, however less in the hospitality. Intercultural communication dimension, and consequently its management is worth exploring field in the case of Swiss hospitality industry. Culturally oriented consumer satisfaction is one of the country priorities for the tourism and hospitality field of the country. This study focuses on the importance of intercultural communication management for satisfying the overseas guests who are taking the leading positions in terms of visits. Correspondingly, since the visitors from the Gulf States take the leading place amongst the consumer segments, they have been chosen as the culturally target audience for this research analysis.